2022
DOI: 10.1111/ina.13011
|View full text |Cite
|
Sign up to set email alerts
|

Indoor green can modify the indoor dust microbial communities

Abstract: Little is known about the potential role of indoor plants in shaping the indoor microbiota. Within the ENVIRONAGE birth cohort, we collected settled dust and performed 16S and ITS amplicon sequencing and qPCR measurements to characterize the indoor microbiota, including bacterial and fungal loads and Chao1 richness, Shannon, and Simpson diversity indices. For 155 households, we obtained information on the number of indoor plants. We performed linear regression models adjusted for several a priori chosen covari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…Unfortunately, Soininen et al (2022) did not sample the green infrastructure system's microbiome and thus cannot trace the origin of the species responsible for the increased skin microbiome diversity, or eliminate the hypothesis that changes to air quality (such as VOC composition (Abis et al 2020;Yuan et al 2017)) as a potential mechanism in altering the composition of human bacterial communities. Correlational survey studies of indoor microbiomes around passive indoor plants have also reported increased environmental microbiome diversity, and similarly did not sample the "source" microbiomes (Dockx et al 2022). Taken together, these studies support hypotheses that urban bioremediation infrastructure could diversify indoor and human microbiomes with measurable benefits to human health outcomes, however the mechanism of diversification requires examination.…”
Section: Urban Bioremediation Infrastructure and Indoor Microbiome Di...mentioning
confidence: 67%
See 2 more Smart Citations
“…Unfortunately, Soininen et al (2022) did not sample the green infrastructure system's microbiome and thus cannot trace the origin of the species responsible for the increased skin microbiome diversity, or eliminate the hypothesis that changes to air quality (such as VOC composition (Abis et al 2020;Yuan et al 2017)) as a potential mechanism in altering the composition of human bacterial communities. Correlational survey studies of indoor microbiomes around passive indoor plants have also reported increased environmental microbiome diversity, and similarly did not sample the "source" microbiomes (Dockx et al 2022). Taken together, these studies support hypotheses that urban bioremediation infrastructure could diversify indoor and human microbiomes with measurable benefits to human health outcomes, however the mechanism of diversification requires examination.…”
Section: Urban Bioremediation Infrastructure and Indoor Microbiome Di...mentioning
confidence: 67%
“…In an attempt to expand upon previous studies that did not report microbiome diversity metrics of indoor green infrastructure (Dockx et al 2022;Soininen et al 2022), this section outlines the methods behind this initial exploration of potential mechanisms and benefits of indoor and human microbiome diversification through the use of indoor urban bioremediation infrastructure. First, taxonomic groups for which there are documented relationships with metrics of either human health or urban bioremediation infrastructure system performance were collected from the literature.…”
Section: Analysis Of Diversitymentioning
confidence: 99%
See 1 more Smart Citation
“…The coating with photochromic microcapsules not only has a photochromic function but is also reversible, so the photochromic coating has a broad application prospect. Research shows that pollution caused by microorganisms in the environment where people live is very severe [24]. Bacteria spread indirectly through surface coatings.…”
Section: Of 23mentioning
confidence: 99%
“…Microbiota of indoor air dust were also studied by characterizing the effects of houseplants on microbiota diversity using rRNA genetargeted metagenomic sequencing. Houseplants were found to increase microbial diversity but not microbial numbers (Dockx et al, 2022). Further, it has been proposed that the rich microbiota of traditional farm homes can protect against asthma, and a farm home-like composition of indoor microbiota may be used as a health-promoting model of indoor microbiota (Ege et al, 2011;Kirjavainen et al, 2019).…”
Section: Figurementioning
confidence: 99%